Dosing patterns and medication adherence in bipolar disorder patients treated with lurasidone: a US retrospective claims database analysis. (December 2016) - Sajatovic, Martha; Ng-Mak, Daisy; Solem, Caitlyn T.; Lin, Fang-Ju; Rajagopalan, Krithika; Loebel, Antony
Background: The aim of this study was to describe dosing patterns and medication adherence among bipolar patients who initiated lurasidone in a real-world setting. Methods: Adult bipolar patients who initiated lurasidone between 1 November 2010 and 31 December 2012 (index period) with 6-month pre- and post-index continuous enrollment were identified from the IMS RWD Adjudicated Claims US database. Patients were grouped by starting lurasidone daily dose: 20 mg (7.1%), 40 mg (62.2%), 60–80 mg (28.7%), and 120–160 mg (2.1%). Patient characteristics were compared across doses using Cochran–Armitage trend tests. Multivariable ordinal logistic regression assessed the association between initial lurasidone dose and patient characteristics. Medication adherence was measured using medication possession ratio (MPR). Results: Of 1114 adult bipolar patients (mean age 40.6 years, 70.6% female), 90% initiated lurasidone at 40 mg or 80 mg/day (mean 51.9 mg/day). Of these, 16.2% initiated lurasidone as monotherapy. Mean lurasidone maintenance dose was 55.2 mg/day and mean MPR was 0.53 [standard deviation (SD) = 0.34] over the 6-month follow up. Substance use, hyperglycemia, obesity, and prior antipsychotic use were associated with higher initial lurasidone doses ( p < 0.05). Odds of a 20 mg/day increase in initial lurasidone dose was 1.6-times higher for patients with substance use [95% confidence interval (CI): 1.16−2.24], 2.6-times higher with hyperglycemia problems (95% CI: 1.15−5.83), 1.7-times higher with obesity (95% CI: 1.05−2.60), and 1.3 (95% CI: 1.01−1.78) and 1.8-times higher (95% CI: 1.17−2.86) with prior use of second- and first-generation antipsychotics, respectively. Conclusions: This real-world analysis of bipolar patients indicated that 40 mg or 80 mg/day were the most common starting doses of lurasidone. A majority of patients used concomitant psychiatric medications (polypharmacy). Higher doses of lurasidone were prescribed to patients with comorbidities or prior antipsychotic use. Adherence to lurasidone was comparable to or better than antipsychotic adherence reported in bipolar disorder literature.